Management of radiation safety by optimizing the parameters of protective structures - Mamontov, O.V.; Malyk, B.O.; Tokarieva, О.V. (Вопросы атомной науки и техники, 2020)
The task of radiation safety management by the optimization of protective structures parameters has been considered. The techniques for calculating the attenuation coefficient of radiation of multilayer floor slabs, the range of constructional materials and the method of the optimization calculation of multilayer protective structures have been analyzed. The analysis has shown that the achievement of the maximum possible efficiency of protection at random distribution of materials is improbable. The optimization task has been solved of the distribution of materials on protective structures and their constructional elements and the list of target functions and restrictions has been made. The algorithm and the program have been developed, the method of optimization calculation of a group of protective structures for the purpose of increasing personnel radiation safety has been improved, and the calculation data testifying the efficiency of the offered approach have been obtained.